Structural basis of fumarate hydratase deficiency. - Picaud, S; Kavanagh, K; Yue, W; Lee, W; Muller-Knapp, S; Gileadi, O; Sacchettini, J; Oppermann, U (Springer Netherlands, 2011)
Fumarate hydratase catalyzes the stereospecific hydration across the olefinic double bond in fumarate leading to L-malate. The enzyme is expressed in mitochondrial and cytosolic compartments, and participates in the Krebs cycle in mitochondria, as well as in regulation of cytosolic fumarate levels. Fumarate hydratase deficiency is an autosomal recessive trait presenting as metabolic disorder with severe encephalopathy, seizures and poor neurological outcome. Heterozygous mutations are associated with a predisposition to cutaneous and uterine leiomyomas and to renal cancer. The crystal structure of human fumarate hydratase shows that mutations can be grouped into two distinct classes either affecting structural integrity of the core enzyme architecture, or are localized around the enzyme active site. An interactive version of this manuscript (which may contain additional mutations appended after acceptance of this manuscript) may be found on the SSIEM website at: http://www.ssiem.org/resources/structures/FH .